PENERAPAN METODE KOPERATIF TIPE STUDENT TEAMS ACHIVEMENT DIVISION (STAD) TERINTEGRASI STRUCTURE EXERCISE METHODE (SEM) UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MATERI SIFAT KOLIGATIF LARUTAN - Ansar A (LPPM Universitas Muhammadiyah Bulukumba, 2022)
This action research aims to improve students' activities and learning outcomes through the application of STAD type cooperative learning integrated with structured exercise method (SEM). The research subjects were 29 students of Class XII MIA2. The procedure for implementing the action used the Kemmis and Mc. Taggart. The action procedure was carried out in two cycles, each cycle consisting of four stages: planning, implementation, observation and reflection. Data collection techniques were carried out through learning outcomes tests and non-tests in the form of observing student activities. The results of the observations showed that the students' activities in learning increased from an average of 54.14 percent(before the action) to 66.2 percent in the first cycle, and to 87.14 percent at the end of the second cycle. Student learning outcomes have increased from an average of 53 before the action, to 72.9 in the first cycle and to 81.3 in the second cycle. Based on the results of the study, it was concluded that: The application of STAD type cooperative learning integrated with the Structure Exercise Method (SEM) can improve the activities and learning outcomes of students of class XII MIA1 SMA Negeri 7 Bulukumba.